Relative longevity of adult Nezara viridula in field cages of cotton, peanut, and soybean. Issue 1 (26th February 2016) - Olson, D.M.; Ruberson, J.R.; Andow, D.A.
Abstract: Producers in the southeastern USA face significant crop losses from the stink bugs Nezara viridula (L.), Euschistus servus (Say), and Chinavia hilaris (Say) (all Hemiptera: Pentatomidae). Cotton, peanut, and soybean are major agronomic crops and host plants of stink bugs in the region. We conducted a field plot study to measure the relative longevity of adult, unmated N. viridula males and females caged on peanut, cotton, and soybean to test three hypotheses: (1) differences in mortality are associated with differences in host plant food suitability, (2) mortality rates increase with age, and (3) males have higher mortality than females. Using survival analysis, we found that the sex of the individual did not affect survival rates on any of the three host plants. Survival was significantly higher in cotton and soybean than in peanut. Mortality rates increased with age in peanut, but not in soybean or cotton. The frequency of canopy temperatures above 35 °C was higher in peanut than in soybean. Peanut appears to be a less than ideal habitat in terms of canopy temperature and/or food quality for N. viridula adults. Both, cotton and soybean were equally suitable food resources for N . viridula adults prior to maturation of the plants.